Bukti Ilegal dalam RUU KUHAP Indonesia: Exclusionary Rules dan Due Process of Law - Nazhif Ali Murtadho, S.H. (Jurnal Penelitian Hukum De Jure, 2025)
The absence of explicit provisions on exclusionary rules in the RUU KUHAP risks enabling the use of unlawfully obtained evidence, undermining due process, violating the presumption of innocence, and eroding the legitimacy of the judiciary. This study aims to analyze the integration of due-process principles and the concept of “unlawful legal evidence” into the RUU KUHAP and to formulate practicable drafting language and operational mechanisms. The method is doctrinal-juridical research employing statutory, conceptual, comparative, and case approaches; primary and secondary materials are analyzed textually, comparatively, and deductively, accompanied by an inventory of legal sources. Findings indicate that the application of exclusionary rules in Indonesia remains sporadic due to a normative vacuum and terminological disparities between “alat bukti” and “barang bukti”; the praperadilan mechanism is not yet capable of substantive review; six elements of due process remain unregulated explicitly; and electronic evidence requires procedural certainty in the aftermath of Putusan MK 20/PUU-XIV/2016. The study concludes that the RUU KUHAP must include an exclusionary-rules clause; define “unlawful legal evidence” and the concept of “batal demi hukum”; strengthen the authority of Praperadilan/Hakim Pemeriksa Pendahuluan; require chain-of-custody procedures and digital forensic certification; and establish sanctions and compensation mechanisms. Recommendations include harmonized drafting, judicial guidelines, training for law-enforcement officers, and independent oversight to restore evidentiary integrity and ensure the protection of human rights.